ILMU ALLAH BERBANDING ILMU MANUSIA (Studi Deskriptif Ayat-ayat Alquran) - Rezi, Muhammad (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2015)
The growth of sciences responses the growth of human brain. As mankind, human being gifted by God many bounties and special features more than other His creatures. This growth make many changes and appearances in many aspects such social, culture, and faith. Human always take many efforts to be better than the other of their species. Observations, writing, and practicing are the sign that human tend to be move the brain. But the most important think should be hold is these all of this world is just the great creatures by someone called Allah who has unlimited access to all of His properties. But the creatures limited verily.